[St.Anns Trinidad, B.W.I.] - (:unkn) unknown (My University, 2010)
The postcard shows a bridge in St.Ann's which is located on the outskirts of Port of Spain
Colour:Black and white; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Suburbs; Cities and towns--St. Ann's